418 A phase 1, dose escalation and dose expansion study of SQZ PBMC HPV as monotherapy and in combination with atezolizumab in HLA-A*02+ Patients with HPV16+ recurrent, or metastatic solid tumors. (10th December 2020) - Eng, Cathy; Baranda, Joaquina; Taylor, Matthew; Gordon, Michael; Matulonis, Ursula; Janku, Filip; Kornacker, Martin; Kamat, Asha; Rosen, Oliver; Jimeno, Antonio; Eng, Cathy
Abstract : Background: SQZ-PBMC-HPV is a therapeutic cancer vaccine created with Cell Squeeze®, a proprietary cell-engineering system. SQZ-PBMC-HPV is a novel cancer vaccine generated from peripheral blood mononuclear cells (PBMC) squeezed with HPV16 E6 and E7 antigens, resulting in delivery into the cytosol. The resulting antigen presenting cells (APCs) provide enhanced antigen presentation on MHC-I to potentially elicit robust, antigen-specific CD8+ T cell responses. Importantly, SQZ-PBMC-HPV are neither genetically modified nor immune effector cells.Studies in MHC-I knockout mice demonstrated that activation of antigen specific CD8+ tumor infiltrating lymphocytes (TILs) was a direct effect of cytosolic antigen delivery to PBMCs. In the murine TC-1 tumor model, tumor regression correlated with an influx of HPV16-specific CD8+ TILs. In vitro studies with human volunteer PBMCs demonstrated that each subset is capable of inducing CD8+ T cell responses. The Phase 1 study includes a significant biomarker program to investigate whether pharmacodynamic effects observed in non-clinical studies correlate with potential clinical benefit. Immunogenic and pharmacodynamic endpoints include Elispot assays to measure frequency of interferon gamma secreting cells, as well as quantification and characterization of TILs and tumor microenvironment. In addition, various cytokine responses and circulating cell-free HPV16 DNA levels in plasma are measured. Methods: SQZ-PBMC-HPV-101 (NCT04084951 ) is open for enrollment to HLA A*02+ patients with HPV16+ recurrent, locally advanced or metastatic solid tumors and includes escalation cohorts for monotherapy and in combination with atezolizumab. After initial demonstration of safety, the study assesses dose effect by testing different cell dose levels, the effect of prolonged antigen priming in Cycle 1 [APC administration on Day 1 only compared to Days 1 and 2 (double priming)] and the impact of treatment duration to identify the optimal dose regimen. The cycle length is 3 weeks, and patients will receive SQZ-PBMC-HPV for up to 1 year or until available autologous drug product is exhausted. Atezolizumab will be administered for up to 1 year. Eligible patients including but not limited to anal, cervical and head and neck tumors will undergo a single leukapheresis at the study site. The manufacturing process includes a maturation step and takes less than 24 hours. The vein-to-vein time for the 1st administration is approximately one week. Patients must have a lesion that can be biopsied with acceptable clinical risk and agree to have a fresh biopsy at Screening and on study. A Study Safety Committee is in place. No formal statistical hypothesis testing will be performed. Results: N/A Conclusions: N/A Trial Registration: NCT04084951 Ethics Approval: The study is registered on clinicaltrials.gov was approved by the Ethics Board of all institution listed as recruiting.